2006
DOI: 10.3904/kjim.2006.21.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Transluminal Removal of a Fractured and Embolized Indwelling Central Venous Catheter in the Pulmonary Artery

Abstract: Vascular catheters are associated with complications such as infection, thrombosis and stenosis. The embolization of a venous catheter fragment is a rare complication. A 39-year-old woman underwent placement of a totally implantable venous access device for chemotherapy to treat a recurrent liposarcoma of the left thigh. The "pinch-off sign" was noted on a routine chest X-ray but that was ignored. Three-months after implantation of the intravenous access device, the indwelling central catheter was fractured an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 11 publications
0
6
0
4
Order By: Relevance
“…These fractures were caused by a chronic compression of the catheter between the clavicle and the first rib, known as a pinch-off syndrome. This syndrome may be prevented by using the jugular access, or else by the implantation of the catheter in the most lateral part of the subclavian vein [16][17][18]. One catheter was disconnected from the reservoir (port) and was removed intact.…”
Section: Discussionmentioning
confidence: 99%
“…These fractures were caused by a chronic compression of the catheter between the clavicle and the first rib, known as a pinch-off syndrome. This syndrome may be prevented by using the jugular access, or else by the implantation of the catheter in the most lateral part of the subclavian vein [16][17][18]. One catheter was disconnected from the reservoir (port) and was removed intact.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Santral venöz port kateterin klavikula ve 1.kot arasında kronik kompresyonu sonucu gelişen kateter kopması ve embolizasyonuna Pinch-off sendromu denmekte olup, nadir görülen (insidansı %1-4.2) fakat ölümcül seyredebilen bir komplikasyondur. [8][9][10] Yapılan bir çalışmada, venöz port implantasyonu gerçekleştirilen 1014 hastanın 11 (%1)'inde venöz port kırılmasına bağlı pinch-off sendromu görüldüğü bildirilmiştir. Bu hastaların yedisinde klinik semptom yok iken, dördünde kateterin pulmoner artere embolize olmasına bağlı semptomlar oluşmuş.…”
Section: Discussionunclassified
“…Percutaneous ICWE removal has now become the preferred technique due to its high rate of success and low rate of complications [54]. Numerous authors have reported successful ICWE retrieval using a variety of endovascular approaches [54][55][56][57][58]. In the majority of such cases, vascular access has been obtained through central veins (e.g., internal jugular, femoral, or subclavian).…”
Section: Intravascular Catheter or Wire Embolization (Icwe)mentioning
confidence: 99%